2006
DOI: 10.1002/pros.20443
|View full text |Cite
|
Sign up to set email alerts
|

PLZF regulates Pbx1 transcription and Pbx1–HoxC8 complex leads to androgen-independent prostate cancer proliferation

Abstract: Androgen-independent cell line DU145 cells lack PLZF gene expression, resulting in the upregulation of Pbx1 and HoxC8 expression. The Pbx1-HoxC8 heterocomplex may lead to androgen-independent growth in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…1). These results are similar to those of previous studies that identified an involvement of PLZF in the oncogenic transformation of prostate (31), colon (32) and leukemic cells (6). …”
Section: Resultssupporting
confidence: 92%
“…1). These results are similar to those of previous studies that identified an involvement of PLZF in the oncogenic transformation of prostate (31), colon (32) and leukemic cells (6). …”
Section: Resultssupporting
confidence: 92%
“…Analysis of PLZF knock-out mice revealed that the protein is a growth inhibitory and proapoptotic factor in the limb bud in vivo [35]. Interestingly, treatment with cannabinoids or overexpression of PLZF inhibits growth of prostate cancer cells [36][37][38]. Together with our results, these findings imply that the action of CB is mediated by the Go/i::PLZF signaling pathway to inhibit cell growth.…”
Section: Discussionsupporting
confidence: 77%
“…Although the role of HOXs in cancer is not fully understood, its aberrant expression is thought to affect pathways that promote tumorigenesis and metastasis (27). For instance, HOXC8 mRNA is overexpressed in prostate cancer cells and is associated with tumor cell proliferation and metastasis (28)(29)(30). In addition, HOXC5 and HOXC8 mRNAs are upregulated in cervical cancer cells (31), and one recent study suggested HOXC10 plays a key role of in the progression and invasion in cervical cancer (32).…”
Section: Discussionmentioning
confidence: 99%